Acero, J.J; Florez, L; Flórez, A. (Ed). (2003). Viejos y nuevos pensamientos. Ensayos sobre la filosofía de Wittgenstein. Granada, España: Editorial Comares. Serie Filosofía Hoy N° 25. 186pp. - Sierra Gutiérrez, Francisco; Pontificia Universidad Javeriana (2004)
null